2006
DOI: 10.1126/science.1130425
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Loops in the Galactic Center: Evidence for Magnetic Flotation

Abstract: The central few hundred parsecs of the Milky Way host a massive black hole and exhibit very violent gas motion and high temperatures in molecular gas. The origin of these properties has been a mystery for the past four decades. Wide-field imaging of the (12)CO (rotational quantum number J = 1 to 0) 2.6-millimeter spectrum has revealed huge loops of dense molecular gas with strong velocity dispersions in the galactic center. We present a magnetic flotation model to explain that the formation of the loops is due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(148 citation statements)
references
References 20 publications
11
136
0
1
Order By: Relevance
“…The model may not be fully appropriate as the interpretation from an observational point. First, the bar potential alone is not able to create high-b features up to 200 pc above the plane; these loops are better explained by the Parker instability (Fukui et al 2006). There is no other driving mechanism known to expel gas up to that height by only stellar gravity.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The model may not be fully appropriate as the interpretation from an observational point. First, the bar potential alone is not able to create high-b features up to 200 pc above the plane; these loops are better explained by the Parker instability (Fukui et al 2006). There is no other driving mechanism known to expel gas up to that height by only stellar gravity.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In fact, Fukui et al (2006) discovered two large molecular loops, loop 1 and loop 2, at a radius of 700-pc from the center, which are triggered by magnetic buoyancy (Parker instability;Parker 1966); while the main focus in Parker (1966) was aimed at the Galactic disk, he already suggested that the magnetic activity might become even more important in the central few 100 pc. Subsequently, Fujishita et al (2009);Torii et al (2010a,b); Riquelme et al (2010); Kudo et al (2011) presented analyses of more detailed observational properties of these molecular loops, and it was shown that the molecular loops are also well reproduced by magneto-hydrodynamical (MHD, hereafter) simulations (Shibata & Matsumoto 1991;Machida et al 2009;Takahashi et al 2009).…”
Section: E-mail: Stakeru@nagoya-ujp (Tks)mentioning
confidence: 99%
See 1 more Smart Citation
“…Using the condition (1.11), we change the above weak form as follows 8) which implies thatũ is a weak solution to (4.1).…”
Section: Linear Instabilitymentioning
confidence: 99%
“…The corresponding compressible isentropic model of (1.1) reads as follows. 8) where µ 0 := µ + ν, ν denotes the bulk viscosity and 3ν + 2µ ≥ 0. The pressure p is usually determined through the equations of state.…”
Section: Introductionmentioning
confidence: 99%